Improving Learning Outcomes on the Theme Caring for Animals and Plants Using the Student Team Achievement Division (STAD) Method for Class II Students at SDN 016 Sungai Pinang: Peningkatan Hasil Belajar Tema Merawat Hewan Dan Tumbuhan Menggunakan Metode Student Team Achievement Division (STAD) Pada Siswa Kelas II SDN 016 Sungai Pinang - Nur Agus Salim; Gamar Al-Haddar; Fitri Maya Sari (Borneo Educational Journal (Borju), 2022)
This study aims to increase students’ achievement in class II of SDN 016 Sungai Pinang in 2018/2019 academic year. The researcher conducted a classroom action research and involved 31 students of class II C as the research subjects. To collect the data, three cycles were applied with four stages; planning, implementation, observation and reflection, through observation, learning achievement test, and documentation. The research result shows that students’ learning achievement increased in each cycle. Students’ average score at cycle 1was 64.67 with 38.70% students passed the minimum grade and 61.29% students failed. Meanwhile, at cycle 2, students’ average score was 68.87 with 58.06% students achieved the passing grade and 41.93% did not. At the third cycle, students’ average score was 74.67 with 83.87% students passed and 16.12% students did not. In the psychomotor domain, cycle 1gained an average value of 54.83 with 19.35%, cycle 2 averaged 70.96 with 80.65%, and third cycle, obtained an average of 79.03 with 96.77%. Affective domain learning outcomes of social attitudes include aspects of honesty, discipline, responsibility, courtesy, caring, self- confidence, and aspects of spiritual attitudes include grateful behavior, praying before and after doing activities, and say greetings when exiting and sntering the room increase in each cycle. In conclusion, STAD method is effective to improve students’ learning achievement especially for students of class II of SDN 016 Sungai Pinang